A study of women consumers in Kota Kinabalu : factors that influence women consumers towards their preference of online shopping / Lily Madeng - Madeng, Lily (2013)
An online shopping system allows a customer to submit online orders for items and/or services from a store that serves both walk-in customers and online customers. The online shopping system presents an online display of an order and an associated delivery window for items selected by the customer (http://forum.jntuworld.com/online-shopping-system). In association to man (manusia), shopping has their own significant relationship as needs and wants are fulfilled when it comes to purchasing products/ services (Dhalokia, 1999). According to (Fram & Axelrod, 1990), the reason why female shop more than male is that they have the primary responsibility for household shopping. There are two (2) types of shopping; Traditional (sometimes Conventional) and Online Shopping. As revolution in technology, especially internet, is advancing, online shopping has gained their popularity among women; It is more convenient and time savvy. However, each of the shopping using Traditional or Online method, has its own pros and cons. In view of that, this study will concerns on what are the factor that influence female consumers to do online shopping, their level of satisfaction towards online shopping and their choices of shopping either through traditional or online approach.